2012
DOI: 10.1074/jbc.m112.365122
|View full text |Cite
|
Sign up to set email alerts
|

Mutations to the Formin Homology 2 Domain of INF2 Protein Have Unexpected Effects on Actin Polymerization and Severing

Abstract: Background: INF2 is a formin protein that accelerates both actin polymerization and depolymerization. Results: Mutations to highly conserved FH2 residues have surprising effects on INF2 biochemical activity. Conclusion: It is dangerous to assume that mutation of conserved FH2 domain residues will have equivalent effects on all formins. Significance: These studies provide mechanistic insight into the role of INF2's FH2 domain in polymerization and depolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Furthermore, we have demonstrated that partial reduction of FMNL1 using RNAi causes any remaining podosomes to become wider in diameter, suggesting that this loss of FMNL1 bundling causes the tightly bundled core filaments to disperse, although this was not seen previously in KO macrophages (Mersich et al, 2010). WH2-like motifs are reported to be important for actin filament severing, including the WH2-like motifs in FMNL3, which are similar to those found in FMNL1 (Heimsath and Higgs, 2012;Ramabhadran et al, 2012;Vaillant et al, 2008). Importantly, mutations of the FH2 domain residue associated with barbed-end binding are not reported to significantly impact severing capacity, unlike mutation of the WH2-like motif (Heimsathand Higgs, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, we have demonstrated that partial reduction of FMNL1 using RNAi causes any remaining podosomes to become wider in diameter, suggesting that this loss of FMNL1 bundling causes the tightly bundled core filaments to disperse, although this was not seen previously in KO macrophages (Mersich et al, 2010). WH2-like motifs are reported to be important for actin filament severing, including the WH2-like motifs in FMNL3, which are similar to those found in FMNL1 (Heimsath and Higgs, 2012;Ramabhadran et al, 2012;Vaillant et al, 2008). Importantly, mutations of the FH2 domain residue associated with barbed-end binding are not reported to significantly impact severing capacity, unlike mutation of the WH2-like motif (Heimsathand Higgs, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Protein Preparation and Purification-All formin constructs were expressed in Rosetta2 Escherichia coli (Stratagene Inc.) as GST fusion proteins, following procedures used previously (22,24,25,28,29). The constructs used were INF2-FFC (FH1-FH2-C construct, human CAAX variant, amino acids 469 -1249), INF2-FC (FH2-C construct, human CAAX, 552-1249), FMNL3-FFC (mouse), mDia1-FFC (mouse), and mDia2-FFC (mouse).…”
Section: Methodsmentioning
confidence: 99%
“…Formins also have essential roles in physiological processes ranging from cell motility in the immune system (Yayoshi-Yamamoto et al, 2000;Eisenmann et al, 2007;Shi et al, 2009), to gastrulation and neural tube closure (Habas et al, 2001;Sato et al, 2006;Lai et al, 2008), heart morphogenesis (Iskratsch et al, 2010;Li et al, 2011), kidney morphogenesis (Brown et al, 2010;Boyer et al, 2011a;Boyer et al, 2011b), and dendritic spine formation in neurons. Some of these functions depend on the actin nucleation and elongation activities of formins (Bartolini et al, 2008;Andrés-Delgado et al, 2010;Madrid et al, 2010;Andrés-Delgado et al, 2012;Ramabhadran et al, 2012;Stastna et al, 2012), which have been demonstrated by investigating point mutations that impair in these activities Lu et al, 2007;Ramabhadran et al, 2012). However, for many of the other in vivo functions of formins, it has not yet been determined which of their activities are required.…”
Section: Cellular Functions Of Forminsmentioning
confidence: 99%
“…Mutation of these residues (e.g. in Bni1, mDia1, mDia2, FRL2, Daam1, INF2) strongly reduces actin nucleation and elongation activities of the respective formins and compromises actin assembly in vivo (Shimada et al, 2004;Xu et al, 2004;Lu et al, 2007;Bartolini et al, 2008;Harris et al, 2010;Ramabhadran et al, 2012).…”
Section: Biochemical Activities Of Forminsmentioning
confidence: 99%